The sun and the wind - Mackinnon, Mairi; Aesop, b.c. 620-560.; Di Chiara, Francesca (London : Usborne, 2008)
A retelling of Aesop's classic tale about a contest between the sun and the wind to see who is stronger.
"Based on a story by Aesop.".
1.7
K-3
Keywords: Fables -- Juvenile literature; Folklore -- Juvenile literature; Fables; Folklore; Fables; Folklore